If Sugar Is Addictive…What Does It Mean for the Law?. Issue 1 (16th April 2013) - Gearhardt, Ashley; Roberts, Michael; Ashe, Marice
Abstract : Newly emerging links between sugar and addiction raise challenging issues for public health policy. What was once a naturally occurring food ingredient is now a highly concentrated food additive. If foods containing artificially high levels of sugar are capable of triggering addictive behaviors, how should policymakers respond? What regulatory steps would be suitable and practical? This paper explores the concept and definition of addiction and presents evidence of the addictive potential of sugar. It also explores the legal implications if sufficient evidence demonstrates that sugar is indeed addictive.